The effect of facilitated tucking on procedural pain control among premature babies. Issue 1 (24th July 2014) - Lopez, Olive; Subramanian, Pathmawathi; Rahmat, Norsiah; Theam, Lim Chin; Chinna, Karuthan; Rosli, Roshaslina
<x xml:space="preserve">Abstract</x> Aims and Objectives To determine the effectiveness of facilitated tucking in reducing pain when venepuncture is being performed on preterm infants. Background Preterm neonates are exposed to a myriad of invasive, often painful, procedures throughout their stay in the neonatal intensive care unit. A growing volume of evidence shows that pain in preterm infants has both short‐ and long‐term deleterious effects. It is within the power and ethical responsibility of neonatal nurses to help premature babies cope with procedural pain. Design A quasi‐experimental study with two groups: control and treatment group. Methods A study was conducted on a cohort of preterm infants (n = 42), divided into control (n = 21) and treatment (n = 21) groups, to determine the effect of facilitated tucking on pain relief during venepuncture on preterm infants in the neonatal intensive care unit. The severity of pain was measured using the Premature Infant Pain Profile score. The primary outcome measure was reduction in the Premature Infant Pain Profile scores. Results The Premature Infant Pain Profile score for the treatment group was significantly lower (M = 6·62, SD 2·598) than for the control group (6·62 ± 2·60 vs. 8·52 ± 2·99, respectively, t = −2·202, p < 0·05). Conclusions Facilitated tucking reduced the Premature Infant Pain Profile scores in preterm infants. Relevance to clinical practice The findings of this study suggest that facilitated tucking is able to alleviate pain; therefore, nurses must be able to carry out facilitated tucking when necessary.